Vocal nodules in children: Laryngoscopic morphological classification aids prognostic judgment - Liu, Jia; Cao, Wei; Sun, Dan-Hua; Wu, Lei; Sun, Jing; Xu, Bin; Fu, Yong (Frontiers in Pediatrics, 2022)
Objective: Vocal fold nodules（VFNs） are benign lesions, occurring at the junction of the anterior and middle thirds of bilateral vocal cords, for which pediatric prognosis and treatment remains controversial. There is a requirement for a correlation indicator to assess the prognosis by pediatric otolaryngologists. Materials and Methods: Patients with VFNs, who were admitted to the department of otolaryngology, were enrolled. The patient’s gender, age, duration of dysphonia, laryngoscopy results and related diseases (allergic rhinitis, sinusitis, laryngopharyngeal reflux) were collected and recovery from dysphonia followed up. Correlations between clinical factors and type of laryngoscopic morphology of VFNs were analyzed. Results: A total of 432 patients with dysphonia were identified, 208 agreed to undergo laryngoscopy and 194 were diagnosed with VFNs as a result. The modal age of patients with dysphonia was between 3 and 7 years with a male: female ratio of 2.1:1 (294:138) and 116 (26.85%; 116/432) had symptoms of allergic rhinitis. The boy to girl ratio among the 194 children with VFNs was about 2.6:1 (140:54) and modal age was consistent with dysphonia. Vocal nodules were the cause of most phonation disorders (93.27%; 194/208) and those with long duration of dysphonia presented more mature (p=0.026) and discrete types (p=0.022). Boys were more likely to have mature (p=0.050) and discrete nodules (p=0.008). Dysphonia recovery time was closely related to age (p=0.000), duration of dysphonia (p=0.000) and morphology of vocal nodules under laryngoscopy (p=0.000). Conclusion: Vocal nodules are the most frequent cause of phonation disorders in children. The morphological classification by endoscopy may help with clinical diagnosis and therapy choice. In the case of the older child with longer duration of dysphonia and the appearance of mature, large, discrete nodules by laryngoscopy, active treatment is recommended, such as drug therapy, voice therapy or surgical treatment.